Anti-Helminthic Activity of Leucas zeylanica Linn Leaves: Anti-Helminthic Activity of Leucas zeylanica Linn Leaves - Radhika, B. (International Journal of Pharmaceutical & Biological Archive, 2018)
The present study was examining the anti-helminthic activity of Leucas zeylanica leaves. For the present investigation, L. zeylanica leaves were collected in the month of January 2017 from Sai Nagar colony of the Karimnagar district. The leaves were dried and made into fine powder and subjected to acetone and ethanolic extraction by soxhlation, the phytochemical screening was done for extracts and the results showed that ethanolic and acetone extracts of the powdered leaves of L. zeylanica showed the presence of carbohydrates, alkaloids, phenols, tannins, flavonoids, steroids, and glycosides. Proteins and amino acids are absent. The extracts were studied for anti-helminthic activity against Indian earthworms Pheretima posthuma, acetone and ethanolic extracts showed the dose-dependent activity by paralysis followed by the death of earthworms. The observation of result shows that the anti-helmintic activity of ethanol extract is more potent compare to the acetone extract. The earthworms were more sensitive to the extracts of ethanol at 20 mg/ml concentrations as compared to the reference drug albendazole (10 mg/ml).